Exploring the relationships among age, spiritual struggles, and health - Krause, Neal M. (Journal of religion, spirituality & aging, 2017)
The purpose of this study is to address two issues. First, an effort is made to see if there are age differences in the prevalence of spiritual struggles. Second, tests are performed to see if age differences exist in the relationship between spiritual struggles and physical health. Data from a recent nationwide survey reveal that younger adults report that they encounter more spiritual struggles than either middle-aged or older adults. The findings further indicate that the negative relationship between spiritual struggles and health tends to become more pronounced at successively older ages.